2013
DOI: 10.1097/jcn.0b013e318260c308
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Disease Knowledge in Dyads of Parents and Their Adolescent Children With Congenital Heart Disease

Abstract: Although parents have significantly greater disease knowledge than their children do, the level of knowledge in both parents and adolescents is suboptimal. Because parents' knowledge influenced their adolescents' knowledge, educational interventions should target both adolescent patients and parents. Transition programs can play a pivotal role in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…However, there were not significant differences between groups in baseline socio‐demographic and clinical variables, but reviewing the baseline distributions of patients' characteristics we observed that although the difference is non‐significant, control group included almost twice as many participants with university degree and half with no formal education. Taking into account the significant positive relationship between education level and knowledge found in previous studies on other diseases (replicated in our completers analysis; in addition, patients with university degree also outperformed no formally educated patients in the variable “feeling informed”), this could suggest that allocation imbalance might have been in fact more prejudicial for the intervention group, in terms of the outcomes evaluated.…”
Section: Discussionsupporting
confidence: 75%
“…However, there were not significant differences between groups in baseline socio‐demographic and clinical variables, but reviewing the baseline distributions of patients' characteristics we observed that although the difference is non‐significant, control group included almost twice as many participants with university degree and half with no formal education. Taking into account the significant positive relationship between education level and knowledge found in previous studies on other diseases (replicated in our completers analysis; in addition, patients with university degree also outperformed no formally educated patients in the variable “feeling informed”), this could suggest that allocation imbalance might have been in fact more prejudicial for the intervention group, in terms of the outcomes evaluated.…”
Section: Discussionsupporting
confidence: 75%
“…Our results show that patients and their parents are often insufficiently informed of the consequences of the treatments they undergo. Our findings of limited knowledge among patients and parents are in line with prior research in (parents of) patients with congenital heart disease 16–18 23–28. Limited knowledge and limited availability of information have been previously described to be associated with anxiety, depression and impaired quality of life, which underlines the importance of adequately informing our patients and their parents 29 30…”
Section: Discussionsupporting
confidence: 86%
“…As this was a Dutch study in which patients/parents were recruited from a single centre, possible international differences in medical practice, culture and language as well as interinstitutional practice variation should be taken into consideration, although our findings are in line with prior studies in other centres and countries 16–18 23–28. Our disease-specific knowledge questionnaire was only aimed at capturing the most basic knowledge of disease, and the level of more in-depth disease-specific knowledge among these subjects remains to be elucidated.…”
Section: Limitationssupporting
confidence: 69%
See 1 more Smart Citation
“…[11] Disparities in the medical care provided to the growing CHD adolescent survivor population involves: (1) poor care transition (an age and developmentally appropriate process, addressing the medical, psychosocial and educational/vocational aspects of care) from child-centered to adult-centered healthcare [8] [ 12] and (2) lack of appropriate transfer of care (the point at which an adult cardiac provider assumes the medical care of a CHD patient). [1,2,[12][13][14] Lack of assessment of transition readiness (TR) (the capacity of the adolescent and medical team to initiate and successfully complete the transition process) [15,16], compounds disparities in quality care. [17] Disparities become further magnified in ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%